Louis, Anja y Sharp, Michelle M. (Eds.): "Multiple Modernities. Carmen de Burgos, Author and Activist". Nueva York, Routledge, 2017. 224 pp - Torres Blanco, Roberto (Cuadernos de Historia Contemporánea, 2019)
Louis, Anja y Sharp, Michelle M. (Eds.): "Multiple Modernities. Carmen de Burgos, Author and Activist". Nueva York, Routledge, 2017. 224 pp